Estudo da situação das escolas estaduais do município de Alegrete com relação à prevenção de incêndio - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The Brazilian forward in the last decades happened in several areas. Education has been greatly revitalized, with major investment in building new schools and universities, and reformation of the ones already built and the consequent increase in the numbers of vacancies. This paper intends to do a study in the five main state schools in the city of Alegrete/RS about the Plan of Prevention Against Fires (Law nº 14.376/2013 and updates), who are following the changes that occur in the past decades in the State of Rio Grande do Sul concerning about the fires in buildings. The PPAF is a legal demand that evaluate all aspects, since prevention of occurrence, as the protection of the people in the building, in case of fire and, also, the containment of the fire. There is a whole culture that needs to be broken about the prevention of fires, because the law of PPAF often don’t happens as a result of the great work for occurrence of adaptations of physical spaces as well as the demand for capital to perform them. In schools these adjustments deserve even greater attention, noted the public would be at risk in the event of a disaster, the vast majority of children and adolescents who have less discernment to act in an emergency. To achieve the objectives of the proposed analysis in this paper, it was used as methodological procedures, as, the bibliographical research, field visits, with data collection and detailed observation of the area studied, data analysis and production of all material that answered to the questions proposed. The analysis in this paper notes that there is no security as required, in the environments that have been the subject of study. The State high school Demetrio Ribeiro (school B) was chosen for the preparation of complete project of PPAF, because it represented the worst level of security between all State schools visited. It is possible to realize, throughout the research, that there is a lack of supervision of the applicable law, because none of the schools is adequately prepared for an emergency situation like this, which puts at risk the lives of several young people and professionals who attend.
Keywords: Civil engineering; Schools; Alegrete; Fire prevention; Engenharia civil; Escolas; Alegrete; Prevenção de incêndio; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL